Stories hidden in tree rings: A review on the application of stable carbon isotopes to dendrosciences - Shestakova, Tatiana A.; Martínez-Sancho, Elisabet (Dendrochronologia (Verona), 2021)
During the last 25 years, the dendrochronology community has benefited from the application of stable carbon isotopes in tree rings to answer a number of research questions, which has resulted in an exponential burst in the number of publications related to this discipline. Here, we perform a literature review of the most influential topics (scope, methodology, targeted species, and climatic signals) that have shaped the research agenda and its impact on the scholarly output over the recent decades. Based on a total of 550 publications, we observed that: (1) conifers are the most investigated tree functional type, being included in over two-thirds of studies; (2) although being a subject of debate, the material of choice for carbon isotope analyses is still cellulose, for which the extraction procedure has been refined with methodological improvements over the years; (3) a shift in the application of carbon isotopes has occurred from proxies of climatic information for paleoclimatic reconstructions to tools for the understanding of short- and long-term tree functioning; and (4) such shift in research scope is apparently linked to an increasing number of publications showing drought-related signals governing isotope time series in the context of current climate change. Besides, we also assessed the number and outcome of publications analyzing 13C-derived intrinsic water-use efficiency (WUEi) trends within the framework formulated by Saurer et al. (2004). We found that leaf intercellular CO2 concentration responding proportionally to the increase in atmospheric CO2 is the most common scenario reported across continents, but with changing importance relative to other scenarios depending on the biome examined. We also detected that climate plays a dominant role over any potential CO2 fertilization linked to increasing WUEi. Looking for new and thrilling research avenues, future studies should further examine δ13C fluctuations at intra-annual resolution, explore its links to wood characteristics, and disentangle δ13C signals of the distinct wood constituents for a better understanding of tree functioning at varying spatiotemporal scales, also benchmarking vegetation models of different complexities.